Finite Element Modeling and Updating of Medium Span Roadbridges. Case study of Ölfusá bridge - Guðni Páll Pálsson 1987- (2012)
Verkefnið er unnið sem lokaverkefni við DTU í Danmörku, í samstarfi við Háskóla Íslands, Vegagerð ríkisins og EFLU verkfræðistofu This thesis focuses on Finite Element (FE) modelling and updating of the Ölfusá suspension bridge in Iceland. This project is part of an ongoing research project undertaken by the Icelandic Road Administration (Vegagerðin) concerning the condition of Ölfusá bridge. The bridge is almost 70 years old and the main cables are not galvanised and showing signs of deterioration. In 1992 the bridge deck was renovated, the new deck is around 50% heavier than the old one and has an unsymmetrical cross section unlike the old one. This lead to increased loading and a change in the distribution of forces in the main cables. To add to all this, the traffic loading has also increased dramatically over the last 70 years. The objective is therefore to determine the current condition of the bridge by updating a FE model. Measurements were performed on the bridge where the modal properties, cable- and hanger forces and deflections were measured. The measurements are presented in chapter 5. The measured modal properties were used to update the FE model and the deflections and forces were compared with the corresponding values from the FE model. The average frequency error between the initial FE model and the measured frequencies was 12% and the modes were not in the correct order. Using manual updating this difference was reduced down to 4,2% and the order of the modes corrected. The FE model was then subjected to automatic updating which lead to an average frequency error of 3%. In the original design the safety factor of the cables was calculated by taking the characteristic strength divided by the characteristic axial force. The safety factor calculated in this way should be around 4. In the design documents the safety factor is determined as 3,93. The safety factor of the main cables for the current state of the bridge calculated using simple hand calculation is 2,49. Using non-linear static ...